Perspectives on the challenges of leadership in schools to improve student learning systems - Ali Taufik; Zen Istiarsono (Institute of Advanced Engineering and Science, 2020)
This study is an analysis of the challenges of leaders in schools to improve learning systems, trying to do an analysis of the six aspects of analysis during the study. The main contribution of this research is related to how to deal with challenges in improving learning systems in schools that have so far faced challenges and obstacles, and these need to be analyzed and solutions. This study uses a qualitative method with a case study model, because this researcher is a case that must be disclosed and found a solution, looking at the gap between quality, performance and leadership in several schools that are the object of research and this research lasted for several years. four months (18 weeks), the time is indeed quite short, but researchers try to use this time effectively to produce something useful. In this case involving eight school leaders, as participants, the results of the application of the six aspects of indicators were able to improve teacher performance and from changes in the learning system as well. can be significantly improved as evidenced by the results of evaluating student learning, this research does indeed need to be deepened comprehensively. The author measures the success rate of these indicators by using a cluster system (individually intervening) individually either for the principal or when assessing students, so the writer can see the improvement.